IS outsourcing and application service provision - Currie, Wendy, 1960-; Seltsikas, Philip (Logistics information management, 2002)
IS outsourcing has been a popular topicwithin the IS community over severaldecades. During the 1970s, the term''facilities management'' was used and theemphasis was on service bureau contracts, where companies would rent space on amainframe owned by the vendor.